Correction to: As-built microstructure and mechanical behavior of Inconel 718 processed via directed energy deposition with laser beam (Progress in Additive Manufacturing, (2025), 10.1007/s40964-025-01054-z) - Cavalcante, Thiago Roberto Felisardo; Bon, Douglas Giovanni; Pascoal, Caio Victor Pereira; Mariani, Fábio Edson; Faria, Guilherme; Coelho, Reginaldo Teixeira; Muñoz, Jairo Alberto; Muñoz, Jessica Calvo; Cabrera, José Maria; Avila, Julian Arnaldo [UNESP] (Springer Nature, 2025)
The publication of this article unfortunately contained mistakes. The funding note was missing. It is given below. This study was financed, in part, by the São Paulo Research Foundation (FAPESP), Brazil. Process Number 2020/09079-2. This study was partly funded by the Conselho Nacional de Desenvolvimento Científico e Tecnológico – CNPq, grant No. 306960/2021–4. Thiago Roberto Felisardo Cavalcante recognizes the financial support through the Ph.D. scholarship from the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance Code 001 and CAPES PrInt, process 88887.886782/2023-00. J. Avila acknowledged the support of the Serra Húnter fellowship. The original article has been corrected.